Periodic health examinations during a pandemic - Janus, Justyna; Kołton, Daria; Kępowicz, Nikoletta; Kobos, Magdalena; Jurkiewicz, Beata (Health Promotion & Physical Activity, 2021)
Introduction: The coronavirus pandemic has changed daily lives. These changes affect many aspects of lives including periodic health examinations. Specialists warn that in the era of the pandemic people abandon examinations. This is a very dangerous phenomenon, which can negatively affect health and general well-being. The aim of this study was to determine the frequency of periodic health examinations during the pandemic period including the use of telephone advice services. Material and methods: The study was carried out in March 2021 among 147 people (120 women and 27 men), in the age range of 18-76 years. The study was carried out by the method of diagnostic survey, with the use of questionnaire technique (authors’ questionnaire). Questions included knowledge of prevention, frequency of periodic health examinations, and health services received by the respondents during the pandemic. Analysis of the survey results provided information on current health problems, time of diagnosis, and course of treatment to date. Results: During the pandemic, the majority of respondents had the opportunity to use a telephone advice, with women more likely to use the telephone advice than men (64.2% vs. 37.0%; p = 0.010). 36.9% of the respondents were satisfied with the service. The main reasons for dissatisfaction with the telephone advice included: inability to examine (33.3%), short telephone advice time (24.2%), misdiagnosis or ineffective treatment (21.2%), long waiting time, difficult contact with the facility (15.2%). Among telephone advice users, 39.1% had chronic diseases; among non- telephone advice users, the percentage was lower at 18.3%. Telephone advice users were significantly less likely to say they did not have periodic health examinations or did not remember when they had them done compared to non- telephone advice users (p = 0.019). Conclusions: During the pandemic, the majority of respondents had the opportunity to use telephone advice. Only 1/3 were satisfied with the telephone advice, and the main reasons for dissatisfaction were as follows: inability to examine, short telephone advice time, misdiagnosis or ineffective treatment. Telephone advice users were significantly less likely to say they did not have periodic examinations or could not remember when they had them done compared to non-telephone advice users.